Severe Hypercapnia Requiring 48-h Whole-Body Hypothermia in an Infant with Acute Bronchiolitis - Michela Librandi; Serena Scapaticci; Valentina Chiavaroli; Altea Petrucci; Paola Cicioni; Rita Cognigni; Francesco Chiarelli; Susanna Di Valerio (MDPI AG, 2022)
Bronchiolitis is a clinical syndrome involving the lower respiratory tract of infants and young children. The majority of patients recover using adequate hydration and oxygen (O2) therapy, while a small number of patients require ventilatory assistance. Beyond these therapeutical approaches, there are no available strategies for patients that do not improve. Hypothermia is a measure used to prevent neonatal hypoxic-ischemic encephalopathy by preventing carbon dioxide (CO2) production and subsequent tissue damage. Other medical applications of hypothermia have been proposed, such as in acute respiratory failure and necrotizing colitis. Case report: We report the case of a 50-day-old girl hospitalized with severe bronchiolitis caused by respiratory syncytial virus. On admission, the girl presented severe hypercapnic respiratory failure, requiring intubation and ventilatory support with conventional and non-conventional systems. However, the patient's general conditions worsened with elevated O2 demand, thus whole-body hypothermia was attempted and performed for 48 h, with a gradual improvement in the respiratory function. No adverse effects were detected. Conclusions: Whole-body hypothermia could have a critical role as a rescue treatment in infants affected by severe hypercapnic respiratory failure, at the expense of few and rare side effects (bradycardia, coagulopathy, hyperglycemia). Notably, beyond reducing CO2 production, whole-body hypothermia might have an impact in restoring lung function in newborns using bronchiolitis refractory to maximal medical therapy and invasive ventilation.